TRADITIONAL AND MODERN APPROACHES TO EXTRACTING LIGNITE-DERIVED HUMIC ACIDS - Avdieieva, Lesia; Makarenko, Andrii; Turchyna, Tetiana; Dekusha, Hanna (European Science, 2025)
This chapter examines traditional and modern methods of extracting humic acids from lignite, a promising raw material for the production of environmentally friendly fertilizers and the regeneration of degraded soils. It describes physico-chemical methods